Hubungan Antara Kinerja Guru Dan Motivasi Belajar Dengan Hasil Belajar Kimia Siswa Pada Materi Asam Basa di SMA N 5 Padang - Widodo, Mugi (RC-INSTITUT, 2019)
The research aims to find the correlation between teachear performance, learning motivation, and chemistry learning achievement on acid based topic in SMAN 5 Padang and their contribution for the learning achivement. The method of the research is correlation reserach with Ex-post factodisign with a quantititative approach. The population of the research are the whole students of grade XII MIA in SMAN 5 Padang for academical year 2018/2019, with the total amount of 178 students. The sampel taken by using clauter random sampling technique with a total of 64 students.Data colection using questionnaire and documentation. Based on the result of the research, it can be concluded that: (1) There is a positive and significant correlation between teacher performance with chemistry learning achievement on acid based topic in SMAN 5 Padang. It can be seen from the data analysis result showed r = 0,42 and t hitung = 3,64. (2) There is a positive and significant correlation between learning motivation with chemistry learning achievement on acid based topic in SMAN 5 Padang. It can be seen from the data analysis result showed r = 0,37 and t count = 3,18. (3) There is a positive and significant correlation between teachear performance and learning motivation with chemistry learning achievement on acid based topic in SMAN 5 Padang. It can be seen from the data analysis result showed r = 0,49 and F count = 9,63.(4) There is constribution between teachear performance withlearning achievement17,6%; constribution between learning motivation with learning achievement14%; and togethers constribution between teachear performance and learning motivation with learning achievement 24,3% Keywords: teachear performance, learning motivation, and chemistry learning achievement